EFFECTIVENESS LEARNING IN HYBRID AGAINST DISCIPLINE STUDY STUDENTS IN COURSES STATISTICS - Antonius KAP Simbolon (Nusantara Hasana Journal, 2023)
There was an outbreak of Covid-19, of course in the world of education give Lots experience new life especially for the community in the world of education. Of all policy government about system learning in the pandemic era , Universitas Prima Indonesia took policy with use system hybrid learning learning so that it is disciplined Study student more easy For noticed and developed as support creation effective learning. Study This addressed For know perception educator to discipline Study student in hybrid learning learning that was carried out at the time this. Approach study This use approach study qualitative with design descriptive. subject study This is fourth semester students who took eye studying statistics in the study program accountancy Universitas Prima Indonesian. Lecturer data collection techniques do experience to student at the time learning hybrid learning with indicator centered discipline learn. Data analysis using data reduction for simplify data presentation and withdrawal conclusion. From the results study about perception educator to discipline Study student in hybrid learning educator learning state that discipline Study student can said as discipline measurable and directed learning with exists planting good discipline to source students from exists a number of factor possible supporters move student For still become discipline student as well as can obey existing regulations made by educators.